Castleman's Disease and Posttransplant Lymphoproliferative Disorder after Liver Transplant: 3-Year Follow-Up. (28th January 2018) - Jha, Lokesh K.; Ulmer, Laura L.; Olivera-Martinez, Marco A.; McCashland, Timothy M.; Fu, Kai; Rochling, Fedja A.
Abstract : A 59-year-old male with a history of hepatitis C cirrhosis and history of hepatitis B exposure presented 8 months after orthotopic liver transplant (LT) with fever, fatigue, myalgia, night sweats, nonproductive cough, and shortness of breath. Bone marrow biopsy for pancytopenia was positive for Epstein-Barr virus (EBV) DNA. Lymph node biopsy for lymphadenopathy on imaging showed human herpes virus 8 (HHV8) associated Castleman's disease. Treatment included valganciclovir, rituximab, and prednisone taper with eventual discontinuation. Quantitative HHV8 DNA was initially 611, 000 DNA copies/mL and was later undetectable at 6 months following treatment and remained undetectable at 3-year follow-up.